Pengaruh Absensi Online “Talenta” dan Motivasi Terhadap Disiplin Kerja Karyawan PT Kia Karawang - Afriyan Deniro Gultom; N. Neni Triana; Thomas Nadeak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study was made to determine the extent of the attendance technology system and work motivation provided by PT KIA Karawang to its employees in improving employee discipline in it. The analysis used in this study is to use independent variables, namely the